Edukasi Media Audiovisual Meningkatkan Kesiapsiagaan Siswa dalam Menghadapi Bencana Gempa Bumi - I Gede Agus Narayana; I Made Sukarja; I Wayan Sukawana; Ni Made Juniari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
As many as 75 percent of schools in Indonesia are located in disaster risk areas that threaten the safety of school children. The high number of victims in school children is influenced by the lack of child preparedness in dealing with disasters. The purpose of this study was to determine the effect of audiovisual media education on the preparedness of elementary school students in dealing with earthquake disasters. The type of research is Pre-Experimental Design with a one-group pre-post design. A sample of 30 students in grades IV and V was taken using a simple random technique. Preparedness data was measured using a questionnaire set by LIPI/ UNESCO/ ISDR in 2006. The results showed that the preparedness of elementary school children before the intervention was given, only 36.7% of students had preparedness with the category of being ready and very prepared in dealing with disasters. After being given education with audiovisual media, most of the students (100%) have preparedness and are very ready to face an earth disaster. The results of the Wilcoxon test got a p-value = 0.00 (alpha = 0.05), so it was concluded that the provision of audiovisual media education significantly increased student preparedness in dealing with earthquake disasters in SD Negeri 1 Lagi Gianyar students. Based on the results of this study, it is recommended for school principals to provide audiovisual media education using existing videos as an effort to increase student preparedness in dealing with earthquake natural disasters in elementary school students.